IL-10 Immunomodulation of Myeloid Cells Regulates a Murine Model of Ovarian Cancer - Hart, Kevin; Byrne, Katelyn; Molloy, Michael; Usherwood, Edward; Berwin, Brent (Frontiers in Immunology, 2011)
Abstract Elevated levels of IL-10 in the microenvironment of human ovarian cancer and murine models of ovarian cancer are well established and correlate with poor clinical prognosis. However, amongst a myriad of immunosuppressive factors, the actual contribution of IL-10 to the ovarian tumor microenvironment, the mechanisms by which it acts, and its possible functional redundancy are unknown. We previously demonstrated that elimination of the MDSC (myeloid-derived suppressor cell) compartment within the ovarian tumor ascites inhibited tumor progression and, intriguingly, significantly decreased local IL-10 levels. Here we identify a novel pathway in which the tumor-infiltrating MDSC are the predominant producers of IL-10 and, importantly, require it to develop their immunosuppressive function in vivo. Importantly, we demonstrate that the role of IL-10 is critical, and not redundant with other immunosuppressive molecules, to in vivo tumor progression: blockade of the IL-10 signaling network results in alleviation of MDSC-mediated immunosuppression, altered T cell phenotype and activity, and improved survival. These studies define IL-10 as a fundamental modulator of both MDSC and T cells within the ovarian tumor microenvironment. Importantly, IL-10 signaling is shown to be necessary to the development and maintenance of a permissive tumor microenvironment and represents a viable target for anti-tumor strategies.